Systematization of work processes in the public management of integrative health practices: an experience report - Lemos, Maria Panisson Kaltbach; Marques, Patrícia Falcão Paredes (Seven Editora, 2023)
Without parameters to carry out personnel dimensioning, to maintain or expand the composition of a management team of integrative practices in public health, this is the first article to present the systematization of the work processes of this type of team, the outline of the steps of identification and prioritization of processes, observation of the current effort by the result, From the vision of the team, and verification of the type of improvement solution for each process, first step to a future sizing of personnel. The methodology described by the Ministry of Health for administrative areas was used. 17 work processes were systematized, all identified by the team with a high level of added value. To improve processes, the need to invest in people was the most frequent, followed by process optimization. The overall result indicated great complexity associated with the work of the team, which has intersectoral actions and great scope of action in the network, at the three levels of health care. The intervention carried out, followed by records and monitoring of activities and results over time, can assist the current and future management of the workforce for integrative practice management teams. DOI:https://doi.org/10.56238/alookdevelopv1-051